2015
DOI: 10.1002/bab.1456
|View full text |Cite
|
Sign up to set email alerts
|

Improved strategy for recombinant production and purification of antimicrobial peptide tachyplesin I and its analogs with high cell selectivity

Abstract: Here, we report an efficient procedure for recombinant production and purification of tachyplesin I (THI) with a final yield of 17 mg/L of the culture medium. The peptide was expressed in Escherichia coli as a part of the thioredoxin fusion protein. With the use of soluble expression followed by immobilized metal-ion affinity chromatography, the recombinant protein cleavage and reversed-phase high-performance liquid chromatography, a yield of THI did not exceed 6.5 mg/L of the culture medium. Further optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…Recombinant tachyplesin I without N-or C-terminal modifications was expressed in Е. coli [9]. The calculated molecular weight of nonmodified and N-and C-terminally modified tachyplesins were 2264.10 and 2305.10 Da, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant tachyplesin I without N-or C-terminal modifications was expressed in Е. coli [9]. The calculated molecular weight of nonmodified and N-and C-terminally modified tachyplesins were 2264.10 and 2305.10 Da, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that tachyplesin I possessed a cytotoxic effect on HL-60 cells (acute human promyelocytic leukemia cells) [11], K562 cells (myelogenous leukemia cells) [10], TSU cells (prostate cancer cells) [1]. The first two studies focused on antitumor activity of natural tachyplesin I with amidated C-terminal residue, in the third report, tachyplesin I with modifications at both termini was used.We have recently developed a novel approach to producing recombinant tachyplesin I analogs [9]. Despite the absence of post-translational C-terminal amidation, the recombinant peptide exhibits both antibacterial and antitumor activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant arenicin-1 and tachyplezin-1 were obtained by heterologous expression in E. coli cells [9,10]. For antibiotic activity assessment, bacterial strains E. coli C600, S. aureus 209P and P. aeruginosa PAO1 were used as test cultures.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, the recombinant MAP30 antimicrobial protein was effectively expressed and targeted to ER in Nicotiana tabacum hairy roots; it exhibited significant antibacterial activity [73], and ER-signal was used for successful expression of a plant defencin protein in transgenic tobacco seeds [53]. However, because AMPs have natural destructive effects on microorganisms and are relatively sensitive to proteolytic degradation, they are often produced by fusion to a partner in heterologous hosts and/or by modifying different parameters during fermentation to obtain successful recombinant production [74][75][76].…”
Section: Peptide Purification and Antimicrobial Activity Evaluationmentioning
confidence: 99%